2012
DOI: 10.1111/j.1447-0594.2012.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dementia: Brazilian version of the Informant Questionnaire on Cognitive Decline on the Elderly and its psychometric properties

Abstract: This study suggests that the IQCODE-BR is a valid tool for screening of dementia and that IQCODE-BR scores do not seem to be influenced by age, educational level and other factors associated with the informants. However, further studies are required to evaluate informant characteristics, such as anxiety states, depression and burden level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…O estudo FIBRA-RJ, deu origem a uma série de artigos, dissertações de mestrado e teses de doutorado. 3,12,[28][29][30][31][32][33][34][35][36] Discussão O estudo FIBRA-BR, por seu delineamento multicêntrico, provavelmente representou um dos esforços mais abrangentes de pesquisadores brasileiros, para a compreensão da dimensão da fragilidade e seus fatores associados, em território nacional. O segmento Rio de Janeiro desse estudo, o FIBRA-RJ, representou uma tentativa de ir além dos objetivos inicialmente traçados, e dar continuidade ao acompanhamento da amostra examinada, investigando outros aspectos de acometimento de saúde, bastante comuns entre a população idosa, e ainda carentes de estudos populacionais com um número substancial de indivíduos.…”
Section: Resultsunclassified
“…O estudo FIBRA-RJ, deu origem a uma série de artigos, dissertações de mestrado e teses de doutorado. 3,12,[28][29][30][31][32][33][34][35][36] Discussão O estudo FIBRA-BR, por seu delineamento multicêntrico, provavelmente representou um dos esforços mais abrangentes de pesquisadores brasileiros, para a compreensão da dimensão da fragilidade e seus fatores associados, em território nacional. O segmento Rio de Janeiro desse estudo, o FIBRA-RJ, representou uma tentativa de ir além dos objetivos inicialmente traçados, e dar continuidade ao acompanhamento da amostra examinada, investigando outros aspectos de acometimento de saúde, bastante comuns entre a população idosa, e ainda carentes de estudos populacionais com um número substancial de indivíduos.…”
Section: Resultsunclassified
“…The IQCODE-BR scores range from zero to 130, and the final score is obtained by adding the values of all the answers to the items, divided by the total number of items. Therefore, low final scores indicate the absence of cognitive deficit (Lourenço & Sanchez, 2014;Sanchez & Lourenço, 2013). It is worth highlighting that the normal distribution of data was tested and confirmed, which enabled the use of the Pearson correlation coefficient.…”
Section: Methodsmentioning
confidence: 95%
“…Scores on the FAQ-BR showed high and statistically significant correlations with scores on the MMSE and the IQCODE-BR. The MMSE is the screening tool for cognitive decline and dementia most widely used in epidemiological studies and showed adequate diagnostic qualities in its validation study for use in Brazil (Lourenço & Veras, 2006), as did the IQCODE-BR (Lourenço & Sanchez, 2014;Sanchez & Lourenço, 2013), also used to detect cognitive decline in the elderly, but based on the informant's report. In light of this, it is possible to state that the FAQ-BR, although it did not demonstrate suitable validity of predictive criteria for dementia, it did show suitable concurrent validity when compared to other tools for screening cognitive decline and/or dementia -based on the report of an informant or not -already validated and in established use in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Jahren wurde bereits hingewiesen. Um langfristige Verläufe zu erfassen und zur besseren Vergleichbarkeit der Ergebnisse, nutzten wir den international üblichen Zeitrahmen von 10 Jahren [16][17][18].…”
Section: Diskussionunclassified